Impact of Performance Appraisal Strategy on Employee’s Job Satisfaction in Ghana Technology University (2015) - Afriyie, Emelia Ohene (Advances in Social Sciences Research Journal, 2015)
Rapid change and development of human resource management practices have made the existence of efficient and effective organisational performance appraisal system for the organisation inevitable. This study is designed to study the relationship between the performance appraisal (PA) strategy and its impact on employee’s job satisfaction. Questionnaire was used for this purpose and the study was conducted at Ghana Technology University Main Campus. Statistical population for this study is 60 employees of Ghana Technology University. SPSS software was used for the analysis. The major findings were that correlation coefficient for the relationship between performance appraisal strategy and employees’ job satisfaction was, however, positive at 0.001. Also, it was found that the relationships between performance appraisal strategy and the employees’ job satisfaction were statistically significant at alpha (α) = 0.01. These indicate, there are positive influences or impact of performance appraisal and employees’ job satisfaction and performance appraisal strategy on job satisfaction and satisfaction on overall position in Ghana Technology University. It is recommended that performance appraisal should be conducted with both managers and employees of Ghana Technology University.